Frailty syndrome and risks for falling in the elderly community - Taguchi, Carlos Kazuo; Menezes, Pedro de Lemos; Melo, Amanda Caroline Souza; Santana, Leonardo Santos de; Conceição, Wesley Rayan Santos; Souza, Gabrielle Feitosa de; Araújo, Brenda Carla Lima; Silva, Allan Robert da (CoDAS (São Paulo), 2022)
ABSTRACT Purpose To identify the prevalence of Frailty Syndrome in the elderly and the relationship with risk of falling. Methods Descriptive, cross-sectional, and analytical clinical study. One hundred and one volunteers over 60 years old were submitted to audiological evaluation, Dynamic Gait Index - Brazilian brief (DGI), Timed Up and Go (TUG) and Edmonton Fragility Scale (EFE) that verified, respectively, hearing thresholds, frailty syndrome, functional and dynamic balance, and risk of falling. The simple percentual distribution, the Wilcoxon´s test and the Bivariate Correlation with Pearson's coefficient were used for statistical analysis. Limits equal to or less than 1.0 and 5.0% were adopted. Results EFE identified 22.8% of volunteers as fragile and 22.8% as vulnerable. DGI and TUG found 34.6% and 84.1% of at risk for falls, respectively. Significant correlations between EFE and DGI (p <0.01), EFE and TUG (p <0.01), and DGI and TUG (p <0.01) were observed. Pearson's coefficient between EFE and DGI, EFE and TUG, and DGI and TUG were -0.26, -0.41, and 0.46, respectively. An association between DGI and TUG and age (p <0.01) was identified. No correlation between EFE and sex or age was found. Conclusion Frailty and pre-frailty were identified in a significant segment of the volunteers, especially in the oldest subjects. Functional and dynamic balance were moderately correlated with frailty, which demonstrated that frailty syndrome increases the risk of falls. RESUMO Objetivo Identificar a prevalência da Síndrome da Fragilidade em idosos e suas relações com o risco para quedas. Método Estudo clínico descritivo, transversal e analítico. Cento e um voluntários com mais de 60 anos, foram submetidos à avaliação audiológica, Dynamic Gait Index – Brazilian brief (DGI), Timed Up and Go(TUG) e Escala de Fragilidade de Edmonton (EFE) que determinaram, respectivamente, os limiares auditivos, síndrome da fragilidade, equilíbrio funcional e dinâmico e risco para quedas. Utilizou-se a distribuição percentual simples, o teste de Wilcoxon e de Correlação Bivariada com coeficiente de Pearson para a análise estatística. Foram adotados limites iguais inferiores a 1,0 e 5,0%. Resultados A EFE identificou 22,8% dos voluntários como frágeis e 22,8% como vulneráveis. O DGI e o TUG classificaram 34,6 e 84,1% de riscos para quedas. Ocorreu correlação significativa entre a EFE e o DGI (p<0,01), a EFE e o TUG (p<0,01) e o DGI e TUG (p<0,01). O coeficiente de Pearson entre EFE e o DGI, entre o EFE e o TUG e DGI e TUG foram -0,26, -0,41 e 0,46 respectivamente. Ocorreu associação entre DGI e TUG e idade (p<0,01). Não houve correlação entre a EFE com sexo e idade. Conclusão A fragilidade e pré-fragilidade foi identificada em uma parcela expressiva dos voluntários, sobretudo nos mais longevos. O equilíbrio funcional e o dinâmico se correlacionaram moderamente com fragilidade, o que demonstrou que a Síndrome da fragilidade aumenta o risco para quedas.